Analisis Struktur Puisi “Sahabat Baik” Karya Tere Liye dengan Pendekatan Objektif - Salma Nur Faridah (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
Poetry is a literary work that has high aesthetics. In contrast to other literary works, such as novels and prose. This can be seen from the structure of the literary works of poetry. In general, poetry is used as an intermediary from the outpouring of the author's heart. It can be expressed in spoken or written form using figurative language and beautiful diction. This difference is not seen from the physical structure, but also from the inner structure of the poem. The main elements in poetry consist of two structures, namely physical and mental. Both have elements that bind each other so that a complete totality of meaning is formed. With that, in interpreting a poem can not be separated from these two elements. With that in mind, in this study the researcher will conduct an analysis of the physical and mental structure of the poem entitled 'Good Friends' by Darwis Tere Liye. With the aim of describing diction, images, concrete words and figurative language as well as describing the themes, feelings, tones and messages contained in the poem. It is hoped that this study can be useful and add insight to readers in the field of literature. In this study using an objective approach. The data source is Tere Liye 'Friend of Biak' poem which was obtained from Tere Liye collection of poems. Based on the results of the analysis it is known that this poem has the theme of harmonious friendship. The poet chooses beautiful language diction through his expertise, knows the meaning of the poem to move the hearts of readers, moves them to maintain the good friends they have. Dervish Tere Liye succeeds in presenting the theme of friendship, a happy tone that is able to inspire the spirit to always appreciate, love and maintain the good friends he has because he is special compared to anything. A good friend is like a historical painting that will always have the most beautiful place for it, even though it already has new things.